2018
DOI: 10.1155/2018/8903021
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of BuqiHuoxueTongluo Formula on Histopathology and Pulmonary Function Test in Bleomycin‐Induced Idiopathic Pulmonary Fibrosis in Rats

Abstract: BuqiHuoxueTongluo Formula (BHTF) is an effective herbal prescription based on traditional Chinese medicine for idiopathic pulmonary fibrosis (IPF). The aim of this study was to elucidate the influence of BHTF on induced IPF model through the aspect of histopathology and pulmonary function test. Wistar rats with bleomycin-induced IPF were given BHTF via intragastric gavage. After 14 days and 28 days of treatment, respectively, on these two time points, we first performed pulmonary function test, performed venti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…In recent years, the position of traditional Chinese medicine (TCM) in the treatment of IPF is becoming more and more important, and the clinical research and meta-analyses have shown that the herbal medicine treating IPF could improve the clinical symptoms, delay the reduction of the lung function, and improve the quality of life of the patients (Yu et al, 2016;Chen et al, 2019;Wu et al, 2019). Many experiments have shown that the herbal medicine has the effects of improving the pathological and pulmonary function of bleomycin-induced IPF rats (Chen et al, 2016;Yu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the position of traditional Chinese medicine (TCM) in the treatment of IPF is becoming more and more important, and the clinical research and meta-analyses have shown that the herbal medicine treating IPF could improve the clinical symptoms, delay the reduction of the lung function, and improve the quality of life of the patients (Yu et al, 2016;Chen et al, 2019;Wu et al, 2019). Many experiments have shown that the herbal medicine has the effects of improving the pathological and pulmonary function of bleomycin-induced IPF rats (Chen et al, 2016;Yu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, many TCMs have been identified to be efficient as anti-fibrosis compounds and also seems to improve lung function along with reduction of dyspnea. Routine clinical treatment of IPF using TCM mainly include decoctions [ 15 ], pills, granules [ 16 ] and injections [ 17 ]. But all of these have limitations, such as poor drug tolerance, inefficient targeted therapy effect, low bioavailability in lungs and hepatoenteric first-pass effect [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the understanding of the pathogenesis of pulmonary fibrosis by traditional Chinese medicine, some progress has been made in the treatment of pulmonary fibrosis with traditional Chinese medicine [6][7][8]. Yifei decoction is a Chinese herbal medicine composed of Cortex Mori, Atractylodes macrocephala Koidz., Fructus Aurantii Immaturus, peach kernel, Salvia miltiorrhiza, Platycodon grandiflorus, and licorice [9].…”
Section: Introductionmentioning
confidence: 99%